Reproductive Biology and Feeding Habits of Razorbelly Scad, Alepes kleinii (Bloch, 1793), in the Northeastern Arabian Sea - Ghosh, Shubhadeep (Journal of coastal research, 2023)
Ghosh, S., 2023. Reproductive biology and feeding habits of razorbelly scad, Alepes kleinii (Bloch, 1793), in the northeastern Arabian Sea. Journal of Coastal Research, 39(6), 1094–1104. Charlotte (North Carolina), ISSN 0749-0208. Alepes kleinii is subject to a commercial fishery in the northern Indian Ocean. The present study provides new information on the diet and reproductive biology of this species, based on the examination of 1109 specimens caught by gillnet off the coast of Veraval (north-eastern Arabian Sea). These samples ranged from 8.6–16.9 cm fork length (LF), and the sex ratio (male:female) was 1:1.45. Females and males reached sexual maturity at 12.25 cm and 12.57 cm LF, respectively. A. kleinii spawn throughout the year, though the peak spawning period was January–March. Monthly percentage of spawning capable individuals ranged from 11.8–60.4% (females) and 12.5–52.6% (males). The gonadosomatic index of females varied from 2.55–6.93, and absolute batch fecundity ranged from 30,653 to 70,275 eggs. Egg diameter (ranging from 230–720 µm) distribution was bimodal with the dominant peak at 601–700 µm, indicating group-synchronous ovarian development. In relation to the diet, A. kleinii <10.0 cm LF were zooplanktivorous, with zooplanktonic crustaceans the predominant prey category; whereas crustaceans were the principal diet of larger (≥10.0 cm LF) individuals followed by juvenile teleosts. Variations in feeding preferences were insignificant with respect to three climatological seasons (18.14%–18.50%) and two length classes (17.73%). Feeding intensity was low, although it increased with fish length, and was at a minimum during the peak spawning months.